2020
DOI: 10.1038/s41420-020-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of phosphatidylethanolamine blunts stress in hepatoma cells exposed to elevated palmitate by targeting the endoplasmic reticulum

Abstract: Genetic obesity increases in liver phosphatidylcholine (PC)/phosphatidylethanolamine (PE) ratio, inducing endoplasmic reticulum (ER) stress without concomitant increase of ER chaperones. Here, it is found that exposing mice to a palm oil-based high fat (HF) diet induced obesity, loss of liver PE, and loss of the ER chaperone Grp78/BiP in pericentral hepatocytes. In Hepa1-6 cells treated with elevated concentration of palmitate to model lipid stress, Grp78/BiP mRNA was increased, indicating onset of stress-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In our study, livers from HFD animals showed a 6-fold increase in TAGs as well as increased levels of FAs, esterified cholesterols and total cholesterol. Changes in liver phospholipids were reflected by a decrease in PE abundance, which is in accordance with a previous study using a lard-based HFD (refer to Table 1 ) [ 52 ]. Synthesis of PE in liver mitochondria is reliant on the activity of mitofusin-2, which is found to be downregulated in HFD-fed individuals [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, livers from HFD animals showed a 6-fold increase in TAGs as well as increased levels of FAs, esterified cholesterols and total cholesterol. Changes in liver phospholipids were reflected by a decrease in PE abundance, which is in accordance with a previous study using a lard-based HFD (refer to Table 1 ) [ 52 ]. Synthesis of PE in liver mitochondria is reliant on the activity of mitofusin-2, which is found to be downregulated in HFD-fed individuals [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…In livers of male and female MC4R-HA +/mice kept on HFD liver abundance of lipid droplets visualized by Nile Red staining was increased by 4.8 G 1.4-fold, p < 0.0001 and by 4.7 G 1.7-fold, p < 0.001, respectively, as compared with that of mice constantly kept on LFD (Figures 6F and 6L). We have found that, in mice exposed to HFD, loss of the ER chaperone Grp78/BiP in pericentral hepatocytes parallels hepatosteatosis (Trentzsch et al, 2020). Abundance of Grp78/BiP in pericentral hepatocytes of male and female MC4R-HA +/mice was decreased by 89.0 G 48.4%, iScience Article p < 0.01 and by 87.0 G 20.0%, p < 0.0001, respectively, as compared with that of mice constantly kept on LFD (Figures 6G and 6M).…”
Section: Exposure To Elevated Palmitate Is Sufficient To Induce Loss Of Coxiv and To Disrupt Mitochondrial Function In Primary Hypothalammentioning
confidence: 90%
“…However, a recent study finds instead that palmitate treatment does not activate a classic UPR with altered ER proteostasis in human SH-SY5Y neuroblastoma cells [16]. We also found that, in hepatoma cells and liver, palmitate treatment failed to induce a classic UPR with increased level of ER chaperones [17]. These observations suggest that ER stress and adaptive responses are dependent on the type of trigger and on the cell type, highlighting the need to validate outcomes of lipid stress in hypothalamic neurons empirically.…”
Section: Introductionmentioning
confidence: 46%